2017
DOI: 10.1007/s12253-017-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

HER2 and TOP2A Gene Amplification and Protein Expression in Upper Tract Urothelial Carcinomas

Abstract: HER2, a potential target for therapy, has been described to be amplified in urothelial carcinomas. As the topoisomerase II alpha (TOP2A) gene is located close to the HER2 gene on chromosome 17q12-q21, it is frequently either co-amplified or deleted with HER2 amplification. The purpose of this study was to assess the impact HER2 and TOP2A gene amplification as well as protein expression on outcomes of upper tract urothelial carcinoma (UTUC). HER2 and TOP2A gene amplification and protein expression were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Yang et al demonstrated that PBK promotes the metastasis of hepatocellular carcinoma by activating the ETV4-uPAR signaling pathway 40 . In addition, TOP2A contributes to the early detection and targeted therapy of a variety of cancers [41][42][43] , including HCC 44 . However, the relationship between some of these genes, such as NEK2, and HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al demonstrated that PBK promotes the metastasis of hepatocellular carcinoma by activating the ETV4-uPAR signaling pathway 40 . In addition, TOP2A contributes to the early detection and targeted therapy of a variety of cancers [41][42][43] , including HCC 44 . However, the relationship between some of these genes, such as NEK2, and HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TOP2A (DNA Topoisomerase II Alpha) amplification was associated with the characteristics of biologically invasive epithelial carcinoma of the urinary tract. Overexpression and/or amplification of TOP2A can help identify whether patients will benefit from targeted therapy [33]. de Resende et al demonstrated that the evaluation of TOP2A protein is of prognostic importance, and because of its relationship with inferior prognosis, the evaluation of TOP2A immunohistochemistry in biopsies can be an meaningful tool for selecting the most appropriate surgical and clinical approaches for prostate cancer patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TOP2α was frequently amplified in bladder tumors (1.5%), particularly in advanced stage tumors (3.4%) (18,33). A recent study also indicated that TOP2α amplification was associated with the biological aggressiveness of upper tract urothelial carcinoma (34). Meanwhile, TOP2α amplification was also observed in a number of other types of cancer, including colorectal cancer (35), breast cancer (36,37), leukemia (38) and prostate cancer (39).…”
Section: Discussionmentioning
confidence: 98%